UJI EFEKTIFITAS ANTIFUNGAL EKSTRAK ETANOL KACANG MERAH (Phaseolus vulgaris L.) Terhadap Candida albicans (in Vitro) - Hidayat, Lukman Hakim; Fitriani, Risa Dwi (E-Prodenta Journal of Dentistry, 2023)
Introductions: Candida albicans can causes an infection called candidiasis. Kidney beans (Phaseolus vulgaris L.) are natural products that contain several active compounds such as saponins, flavonoids, tannins, and coumarins that can damage the membrane and cell wall of Candida albicans. Methods: The design of this study used true experimental post control design only with the tube dilution method. Extract concentrations used were 3200 mg/ml, 3600 mg/ml, 4000 mg/ml, 4400 mg/ml, 4800 mg/ml, 5200 mg/ml, 5600 mg/ml, and 6000 mg/ml. This study used a negative control (extract 0%) and a positive control (Nystatin 1%), each of which was added with Candida albicans. Results: The results showed that the Minimum Inhibitory Concentration (MIC) was obtained at 5200 mg/ml and the Minimum Bactericidal Concentration (MBC) was obtained at 6000 mg/ml. One Way ANOVA statistical test results showed a significant difference (significance value 0,000; p< 0.05). Pearson correlation test showed the direction of the negative correlation (r = -0.945; p <0.01). Discussion: The ability of ethanolic extract of kidney bean to inhibit growth and kill the Candida albicans is due to the active compounds contained in it, namely flavonoids, saponins, tannins, and coumarin. Flavonoids can cause protein denaturation. Saponins have the ability to kill Candida albicans by forming pores in the double lipidic layer that results on the loss of cell integrity. Tannins have the ability to inhibit fungal growth by inhibiting the synthesis of chitin and damaging cell membranes. Coumarins can cause fungal death by interfering with cell wall synthesis. Conclusions: The conclusion of this research is the ethanol extract of kidney bean can inhibit at the concentration of 5200 mg/ml and kill the growth of Candida albicans at the concentration of 6000 mg/ml.